The Effect of auriculotherapy on sleep quality in children with attention deficit hyperactivity disorder: a randomized clinical trial - Laleh Mohammadi; Zahra Tagharrobi; Khadijeh Sharifi; Zahra Sooki; Mohammad Zare; Fatemeh Zare Joshaghani (BMC Pediatrics)
Abstract Introduction Considering the importance of sleep disorders in children with attention-deficit/hyperactivity disorder (ADHD) and effective therapeutic strategies, the present study aimed to investigate the effects of auriculotherapy on sleep quality in children with ADHD. Materials and methods This clinical trial was conducted in children with ADHD in Kashan, Iran, 2021–2022. Fifty-two eligible samples were selected using convenience sampling and randomly assigned to intervention and sham groups. The intervention group used Vacaria seeds to apply ear acupressure to Shenmen, Sympathetic, Subcortex, Heart, and Endocrine points for four weeks, while the sham group received adhesives without seeds and pressure. Sleep quality was assessed using children’s sleep habits questionnaire at the beginning (T0), at the end of the intervention (T1), and one month later (T2). Data from 45 children (23 and 22 children in the intervention and sham groups, respectively) were analyzed using the per-protocol and intention-to-treat designs using repeated measures analysis of variance. Results The background variables did not significantly differ between two groups. The between-group analysis revealed a significant interaction effect of time and intervention on sleep quality (Effect Size = 0.545, p < 0.0001). The sleep quality score in the intervention group was significantly greater than in the sham group at T1 and T2 (p < 0.0001). The within-group analysis of the intervention group revealed a significant difference in sleep quality scores at three time points (Effect Size = 0.672, p < 0.05). In the sham group, sleep quality score increased significantly over time (Effect Size = 0.511, p < 0.05). Conclusions The findings suggest that auriculotherapy may be a beneficial complementary treatment for improving sleep quality in children with ADHD.